Tata Kelola Perbatasan Indonesia-Papua Nugini: Model Kerja Sama Strategis Terintegrasi - Abdullah Afif Thaifury; Ananda Yuvino Putra Permadi (PT. Data Jaringan Visual Indonesia (Djava), 2026)
This research discusses strategic cooperation opportunities between Indonesia and Papua New Guinea through the perspective of modern border theory. Border areas are no longer viewed solely as security zones, but also as spaces for economic, social, cultural, and political interaction that can support regional stability. The study applies a qualitative descriptive approach using literature review from academic journals, books, policy documents, and previous studies concerning border governance and Indonesia–Papua New Guinea relations. The analysis uses borderlands theory and the Integrated Border Management (IBM) approach to explain how border management can balance security interests with community welfare and economic development. The findings show that cross-border economic cooperation, infrastructure connectivity, and community-based development programs have the potential to strengthen bilateral relations and improve welfare in border regions. In addition, closer cooperation in diplomacy and security may help reduce transnational crime, illegal border crossings, and political tensions related to the Papua issue. The study concludes that the Indonesia–Papua New Guinea border should be managed as a shared development space that provides mutual economic, geopolitical, and security benefits for both countries.